Microcontroller based variable gate voltage for MOSFET - Nuripaizail, Ahmad (2008)
Metal Oxide Semiconductor Field Effect Transistor, MOSFETs are important and expansive switching devices in many power electronic circuit applications. MOSFETs require adequate pulses at its gate terminal in order to work properly. The amount of current going through the source and drain terminals is controlled by the magnitude pulses supplied. Normally, the magnitude of gate pulses is fixed and set to a nearly maximum allowable current of MOSFET. The problem with fixed type gate pulses is whenever overload occurs; the MOSFETs may experience very high current and thus working beyond their safe operating area (SOA). This situation might destroy the MOSFET. This project is implement base on PIC16F84A to generate PWM. The IR2109 use provide variable magnitude of PWM pulses and then to drive the based gate of the MOSFET. IR2109 is selected because of its ability to withstand high voltage input.